NUTRACEUTICAL STUDIES ON PASSIFLORA EDULIS – PASSION FRUIT - V. N. ARIHARAN; V. N. MEENA DEVI; P. NAGENDRA PRASAD (International Journal of Pharma and Bio Sciences, 2013)
An ethno botanical survey was conducted in order to explore the ethno medicinal plants used by the Kani tribal people in Pechipparai forest range (Southern western Ghats) in Kanyakumari District of Tamilnadu, South India. During the survey, the author’s documented 15 plants belong to eight different families which are having fruits with medicinal and nutritional value. Passiflora edulis is one which looks like an ornamental plant but the fruits are having high medicinal values. It also contains high amount of vitamin C in the fruits. The fruit is used as a heart tonic, digestive stimulant, body cooling, anti-asthmatic, bronchitis, diuretic and anti oxidant. The nutrabolic content, the medicinal uses and the cultivation methods are given in this communication.